Proposal For A Priority Site For The Conservation Of Biodiversity In The Huancavelica Region – Peru - Varga, Doris Esenarro; Leon, Karen Huachaca; Pandey, Bishwajeet; Amaya, Pedro; Carranza, Carlos Francisco Cabrera (The journal of contemporary issues in business and government, 2021)
This research aims to propose a priority site for biodiversity conservation in the region of Huancavelica - Peru, using the methodology of fine filtering through the analysis of biodiversity, delimiting the proposal area, identifying the objects of conservation, sources of pressure, and threats of ecological processes; and zoning according to the legal regulations of SERNANP. Using digital tools such as ArcMap, Google Earth, SASPlanet, Microsoft Excel, and state geoportals such as SERNANP, MINAM, and IUCN. Besides suggesting a conservation area in Huancavelica, the study aims to stimulate research in the design of natural protected areas (NPA) in the country with the ultimate goal of conserving biodiversity, allowing better management of natural resources. The results show that the priority site would be located within the provinces of Castrovirreyna and Huancavelica with an area of 179 227.92 ha, identified 6 objects of conservation of cultural, natural and ecosystem aspects, among the sources of pressure, is the sustainable agricultural expansion, the development of road infrastructure projects, mining or other liabilities in which there is a change of land use and poaching and indiscriminate.